1993
DOI: 10.1104/pp.101.1.267
|View full text |Cite
|
Sign up to set email alerts
|

Lipids, Proteins, and Structure of Seed Oil Bodies from Diverse Species

Abstract: Oil bodies isolated from the mature seeds of rape (Brassica napus L.), mustard (Brassica juncea l.), cotton (Gossypium hirsutum L.), flax (Linus usifafis simum), maize (Zea mays L.), peanut (Arachis hypogaea L.), and sesame (Sesamum indicum L.) had average diameters that were different but within a narrow range (0.6-2.0 fim), as measured from electron micrographs of seria1 sections. Their contents of triacylglycerols (TAC), phospholipids, and proteins (oleosins) were correlated with their sizes. The correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
369
13
20

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(430 citation statements)
references
References 16 publications
28
369
13
20
Order By: Relevance
“…In addition to changes in the NDF fraction, the only other measurable difference we observed in transgenic soybean was a significant increase in oil body size. Tzen et al (1993) reported that oil bodies from different species had average diameters that were different, but the differences were within a narrow range (0.6-2.0 mm). While we observed a similar range of oil body sizes in control soybean (0.72-2.5 mm), the oil bodies in our transgenic soy were significantly larger (1-14 mm).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in the NDF fraction, the only other measurable difference we observed in transgenic soybean was a significant increase in oil body size. Tzen et al (1993) reported that oil bodies from different species had average diameters that were different, but the differences were within a narrow range (0.6-2.0 mm). While we observed a similar range of oil body sizes in control soybean (0.72-2.5 mm), the oil bodies in our transgenic soy were significantly larger (1-14 mm).…”
Section: Discussionmentioning
confidence: 99%
“…have a narrow size range within a species (Tzen et al, 1993). Physcomitrella might not have evolved a mechanism to control the sizes of OBs.…”
Section: Discussionmentioning
confidence: 99%
“…Aleurone layers were separated from kernels harvested at 35 dap. At this stage of maturation, most of the oils and oleosins had been synthesized (Tzen et aL, 1993), and the kernels were still sufficiently soft such that the aleurone layers could be removed.…”
Section: Plant Materialsmentioning
confidence: 99%